Popiacarbonarabynis / Muhammad Aliff Aminuddin ... [et al.] - Aminuddin, Muhammad Aliff; Abdullah, Nor Faidah; Mazlan, Nurul Aqilah; Mohd Idris, Aleesya Aina; Mustafa, Ahmad Naqiuddin (2021)
This case study was made to examine the problems and stories behind the established business. This study has selected a small business that is POPIACARBONARABYNIS as a small business to discuss the issue. Through this case study, we will be able to see the history of POPIACARBONARABYNIS established and cultivated to this day. Not only that, but we will also study the problems faced by this business as well as recommendations that can be proposed to solve the issues and problems found in the business owned by a nurse living in Johor Bahru. Through this study, we can know that the founder is a nursing diploma graduate student and started this business a long time ago. This business has also sold at a reasonable price and is very worthwhile causing it to sell well in the market. The popia carbonara business also uses social media as their marketing strategy to promote their products to the public. Not only that, but the founder will also send stock to the grocery store owned by his friends and the founder has parents who enter the world of small business and gives an opportunity to the founder named Nisa. In addition, we can find out the financial achievement obtained by this popia carbonara business. Through this study, we will be able to see and present a SWOT analysis approach for this business. The strength of this business is that the founder knows the target market that needs to be focused on and the founder produces rare and rare products while using innovative techniques on his product to attract new and regular customers. Problems or weaknesses found in this business are limited movement in some states due to MCO, difficult to get raw materials of the product and riders that lack experience in delivering the products. Opportunities that can be found are most of her audiences are wide that came from family, friends and current audience, she has a permanent rider to handle all the delivery services, and, in her house, she has her own special refrigerators supported by parents to keep the inventories/stocks of popia raw materials. Threat to this business is few entrepreneurs that are making the same businesses and she had preferred the online banking system instead of cash since the outbreak of Covid-19. The major problem that “Popiacarbonarabynis” frequently faced is the issue on understaffing and product handling by staffs. The agent and customer demand are way over her usual capacity in producing. And because of that she is required to produce fresh batches of her product almost every day. The founder was a nurse and with this problem she had to hire some staff to meet the demands of customers and agents and caused her to have to exert her energy and that of her sister and their staff to complete the order. Nisa has tried to provide stock to be stored for the next batch, but it is always sold out and causes her to make popia products every day. In addition, the problem is the handling of the product by its staff. This is due to several food delivery runners failing to provide excellent product quality to customers as displayed in advertisements. Nisa found out about this issue through customer feedback.